Unactivated alkyl halides in transition-metal-catalyzed C-H bond alkylation - Ankade, Shidheshwar B.; Shabade, Anand B.; Soni, Vineeta; Punji, Benudhar (ACS Catalysis, 2021)
Alkylation represents an important organic transformation in molecular science to develop privileged alkylated arenes and heteroarenes. Especially, the direct C-H bond alkylation using unactivated alkyl halides is a straightforward and attractive approach from both the step-economy and chemoselectivity perspectives. Substantial progress has been made in the direct alkylation using primary, secondary, and tertiary alkyl halides along with the methylation and fluoroalkylation. This Review broadly summarizes the transition-metal-catalyzed alkylations of C-H bonds on various arenes and heteroarenes with unactivated alkyl halides until October 2020. On the basis of the substrates utilized for alkylation, the Review is divided into two major sections: alkylation of arenes and alkylation of heteroarenes.
Keywords: (hetero)arenes; Alkylation; C-H activation; transition metals; unactivated alkyl halides

Nickel-catalyzed branch-selective C-H alkylation of indoles and azoles with alkenes: an additive- and solvent-free approach - Ankade, Shidheshwar B.; Banerjee, Shuvajit; Punji, Benudhar (European Journal of Organic Chemistry, 2024)
The development of sustainable protocols for the synthesis of alkylated heteroarenes is crucial owing to their widespread existence in medicinally relevant and bioactive natural products. Herein, we describe an efficient, additive- and solvent-free approach for the regioselective C-H alkylation of indoles and azoles with alkenes using a nickel catalyst, which proceeds through a chelation-assistance strategy. The reaction exclusively provided branched alkylated products with the compatibility of alkyl, alkoxy, fluoro, trifluoromethyl, alkene, cyano, ester, and carbonyl groups. This protocol is applicable to other heteroarenes, such as imidazoles and benzimidazoles, providing the desired alkylated products with exclusive Markovnikov selectivity. The synthetic utility and scale-up of the reaction are demonstrated, and the protocol is in concord with the principles of green chemistry. Alkylation proceeds through facile and reversible C-H nickelation and alkene insertion processes, presumably involving rate-limiting reductive elimination. A straightforward nickel-catalyzed protocol for the C-H alkylation of indoles and azoles is disclosed that proceeds under additive- and solvent-free conditions. The reaction utilizes readily available alkenes as alkylating partners and delivers Markovnikov products with tolerance of sensitive functionalities. image
Keywords: Alkylation; branch selectivity; indoles; Nickel; solvent-free synthesis